Operative Techniques in Single Incision Laparoscopic Colorectal Surgery (Springer International Publishing, 2018)
The goal of this text is to expand one's practice of minimally invasive colorectal surgery by implementation of various advanced reduced port and single techniques. The authors present a comprehensive operative technique text to teach and implement single incision and reduced port laparoscopic colorectal surgery best practices into clinical practice. The text is divided into three main sections: perioperative considerations; focused operative techniques, tips and tricks; and step-by-step details of common colorectal procedures. Each case is paired with intraoperative photos and video accompaniment to facilitate understanding the technique, reproducing the steps, and implementing single incision laparoscopic colorectal surgery. The extensive illustrations and links to video make this a truly interactive text. With the aid of this text, surgeon experienced in laparoscopy, as well as those looking to expand their minimally invasive arsenal will be able to successfully incorporate single incision laparoscopic techniques into practice .